STRATEGI GURU DALAM MENGEMBANGKAN SELF-REGULATION EMOSIONAL SISWA DI MADRASAH IBTIDAIYAH NURUL ITTIHAD KOTA JAMBI - Syasqi Fadwina; Sri Yulia; Paujan Azim (STKIP Pesisir Selatan, 2026)
Developing emotional self-regulation skills in elementary school students is a crucial aspect in shaping their character, discipline, and social skills. However, in practice, students still experience difficulties in controlling their emotions, such as irritability, difficulty controlling themselves, and a lack of ability to respond appropriately to situations. This situation demonstrates the importance of teachers' roles and strategies in guiding students' emotional development. This study aims to analyze teachers' strategies in developing students' emotional self-regulation at Nurul Ittihad Elementary Madrasah in Jambi City. This study used a qualitative approach with a case study method. The research subjects consisted of fourth-grade teachers, students, and the madrasah principal. Data collection was conducted through observation, in-depth interviews, and documentation. Data were analyzed using interactive analysis techniques that include data reduction, data presentation, and drawing conclusions by ensuring data validity through triangulation of sources and techniques. The results of the study indicate that teachers' strategies in developing students' emotional self-regulation are implemented through several main approaches, namely teacher role models in controlling emotions, habituating positive behavior in learning activities, providing motivation and positive reinforcement, and integrating religious values ​​into madrasah activities.